Perancangan Website Penjualan Toko Online Pada Toko Usaha Tani Mandiri Sintang Dengan Menggunakan Framework Codeigniter - -, Dany Fahrurrozi; David David; Gusti Syarifudin; Sandy Kosasi; Susanti Margaretha Kuway (Jurnal Informatika dan Komputer, 2024)
The Mandiri Farming Business Store has a need to be able to increase sales, manage goods/products so that they can be conditioned, and sales or marketing that is classified as conventional, which causes human error and farmers who have to come all the way to the store to get product information. This research aims to build a codeigniter-based sales website that has an MVC concept and a product recommendation system. This will simplify the shop activity process. The scope of the research uses the CodeIgniter framework which has an MVC concept and a product recommendation system to build sales websites. Using the midtrans API as a payment gateway. The form of research used is a case study. The research method used is DSR (Design Science Research). The design method used is the Agile Extreme Programming (XP) method. The results of this research produced a fertilizer and plant seed sales website that provides product and goods information to buyers and makes it easier for buyers to make purchases online. The conclusion of this research is that it facilitates sales and purchase transaction activities in stores. This research suggests adding other features such as delivery services.